PEMBUATAN PIRANTI “URUP-URIP” PENYINARAN UV BERTENAGA SURYA: UPAYA STERILISASI BAKTERI PADA HASIL PANEN TANAMAN SAYUR DI CIANJUR, JAWA BARAT - Wegig Murwonugroho; Setia Gunawan; Astri Rinanti (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
The problems generally faced by farmers are that vegetables easily rotting due to delayed selling time and higher hygienic standard of vegetables. Based on an interview, we acknowledge that the farmers are unable to understand the utilization of ultraviolet irradiation technology. UV irradiation facilities - which help kills various types of bacteria, spores, protozoan viruses and algae - should be placed near vegetable harvest location. The physical part of vegetables requires special attention and they should not be moved on a regular basis to prevent damages. However, the harvest location is quite distant from electricity sources. As a solution to overcome this problem, a solar powered UV irrayer facility equipped with a portable bag is required. Besides that, the tool should be fitted with branded plastic casings to hold the vegetable to improve selling value, safety, and readiness of the vegetables. The objective of the utilization of this appropriate technology is to improve the quality of the harvested crops. Vegetables will be free from bacteria and risks of Covid-19 exposures. The target of this program is to improve vegetable selling sales rate and to improve the prosperity of the farmers better, or at least as high as pre-pandemic era. The method used to procure this appropriate technology is a design thinking method that covers empathy, define, ideate, prototype, and testing. The implementation of the counseling and training activities were conducted on-line and off-line whilst also applying a strict health protocol. The activity was conducted for 4 months.